Feeding combination of Lactobacillus casei and extracts of dahlia tuber or garlic on intestinal bacteria, nutrients digestibility and performance of broiler chickens - Istna Mangisah; Nyoman Suthama; Heni Rizqiati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
This study aimed to evaluate the effect of dietary inclusion of 2% synbiotic (Lactobacillus casei + dahlia tuber extract/LEDT or Lactobacillus casei + garlic extract/LEGT) on intestinal bacteria, nutrient digestibility, and growth of broiler chickens. A total of 150 birds of one-day-old male Cobb broiler were randomly assigned into three groups of treatment with five replications (10 birds each). Dietary treatments applied were T0 = basal ration, T1 = basal ration + 2% LEDT, T2 = basal ration + 2% LEGT. Synbiotics were given to starter chicken (from 2 to 3 weeks old). Parameters observed were intestinal bacteria (total lactic acid bacteria/LAB and coliform counts), nutrients digestibility, and body weight. Data were subjected to analysis of variance and followed by Duncan test. The results showed that the population of intestinal LAB in synbiotic-treated birds significantly (P<0.05) increased while coliform decreased as compared to control group. Protein and crude fiber digestibilities, and growth of broiler chickens given dietary inclusion of synbiotic either LEDT or LEGT were also significantly (P<0.05) higher than those fed control diet. In conclusion, dietary inclusion of 2% synbiotic LEDT increase body weight of broiler chickens through the improved balance of intestinal microbiota and nutrients digestibility.